PARADIGMA LIBERAL ARTS DALAM PENDIDIKAN DI ERA DISRUPSI STUDI KASUS DI ZAYTUNA COLLEGE - Kurniawan Dwi Saputra (Profetika: Jurnal Studi Islam, 2020)
Amidst the noisy discourse of disruption era, the orientation of education in Indonesia is in a crossed way. On the one hand, by the presidential regulation number 87 on 2017, the government wants indonesian education to foster its character education. On the other hand, the more pragmatic approach to prepare skill-based system of education as the answer to industrial demands is obvious in the more recent government discourse. Based on this background, this qualitative research tries to present liberal arts education paradigm as an alternative way to today’s form of education. By studying relevant literature resources, and by evaluating its practice in Zaytuna College as the case, this research argues that liberal arts education is in line with core principles in Islamic education which views human as holistic creatures with many potentials.